PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA OPERASI BANK SEBELUM, SELAMA, DAN SESUDAH KRISIS KEUANGAN - Ayu Fitri Febriani; Abdul Rohman (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to see the effect of corporate governance on bank operating performance before, during, and after the financial crisis. The dependent variable used in this study is bank operating performance as measured by capital adequacy ratio, asset growth ratio, management quality, profitability ratio, and liquidity ratio, while the independent variables are god characteristics, ownership structure, company disclosure, and CEO education, and bank size and bank age as a control variable.The research sample is 7 banks listed on the Indonesia Stock Exchange (IDX) in 2004 - 2012. The data used are secondary data and the selection of samples using purposive sampling method. The analytical method used in this study is multiple regression analysis. Before being conducted by regression test, it was examined by using the classical assumption tests.The results of this study indicate that not all independent variables in the study, namely board characteristics, ownership structure, company disclosure, and CEO education have a significant effect on bank operating performance both before, during, and after the financial crisis.